The Improvement of the Image by Using MATLAB - Hariza, Haimi (Universiti Malaysia Sarawak, (UNIMAS), 2006)
Image enhancement through noise reduction is a fundamental problem in image processing. Noise reduction is a technique to recover an original image from a degraded one. Basically, this project is focusing on impulsive noise reduction using a nonlinear Spatial filtering whereby an algorithm will be implemented to solve problem faced with standard Median Filter. The Median Filter was once the most popular nonlinear filtering for removing impulsive noise with less blurring compared to linear smoothing filters. However, when the noise level is greater than 0.20, some details and edges of the original image are degraded by this filter. Therefore, the intention of this project is to implement an Adaptive Median Filter with a variable window size using Matlab software. Lastly, the output image of the Adaptive Median filter will be proved better because this filter design can provide an excellent result in removing the impulse noise as well as preserving the sharpness and details in the filtered image even after being processed repeatedly. In addition, the general comparison between the performance of linear filters and non linear filters will also be discussed to prove that the Adaptive Median Filter is the best technique for impulsive noise removal